MANAJEMEN WIRELESS DENGAN MAPPING SSID ACCESS POINT PADA STMIK LOMBOK - Ahmad Tantoni; Mohammad Taufan Asri Zaen (Jurnal Informatika dan Rekayasa Elektronik, 2019)
The wireless network at STMIK Lombok is connected to the local server network and the internet with the spread of access points in several buildings. In some parts of the building have different strengths and the access point or wireless signal strengths, some have broad and strong signal coverage, but there are also areas that have limited / weak signal coverage, even no wireless or blank-spot signal. This blank spot can be caused by many obstacles, including walls, tiles, trees, and others. Based on observations at STMIK Lombok, wireless signal coverage has not been able to cover the entire campus building area; many are unstable and tend to be weak. Therefore, wireless management research was conducted by mapping the SSID access point which is expected to offer/give a solution so that the wireless signal can cover all STMIK Lombok campus buildings. Wireless management by mapping SSID access points on STMIK Lombok provides a solution for location placement and number of access points to be installed so that the campus area of ​​STMIK Lombok can be covered by wireless networks. Keywords : wireless, wireless network, mapping SSID, access point, MikroTik